Comparison between Intermittent Propofol Bolus Techniques and Target-Controlled Infusion in Patients Underwent Gastrointestinal Endoscopy - Arif HM Marsaban; Luki Sumaratih; Pryambodho Pryambodho (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Nowadays, the use of propofol for sedation during gastrointestinal endoscopic procedure has become more popular, either by intermittent-bolus (IB) technique or target-controlled infusion (TCI). Theaim of this study was to compare the outcomes of both techniques including the total consumption of propofol, consumption per minute, total cost, side effects and its recovery time.Method: This study was a single-blinded randomized clinical trial conducted at Digestive Endoscopy Center, Cipto Mangunkusumo Hospital, Jakarta between October and November 2013. There were fifty patients with pre-operative American Society of Anesthesiologist (ASA) Physical Status Classification I-III, aged 18-65 years, body mass index 18-30 kg/m2 who were randomized to obtain sedation with IB propofol or TCI after having a premedication with 1 μg/kgBW fentanyl. The outcomes including the duration of sedation, total dose, propofol consumption per minute, the total cost, the incidence of hypotension, the incidence of desaturation, and recovery time were then evaluated using SPSS version 21.0.Results: Duration of procedure between two groups was not significantly different (p = 0.718). Total dose of propofol, its consumption per minute and total cost were higher in TCI group (p = 0.010; p = 0.004; p = 0.001). The incidence of hypotension, desaturation and recovery time were not significantly different (p = 0.248; p = 0.609; p = 0.33) in both groups.Conclusion: IB technique is more efficient in terms of total propofol dose, consumption per minute and total cost compared to the TCI technique. The incidences of hypotension, desaturation and recovery time profiles were comparable between the two groups.Keywords: gastrointestinal endoscopy, intermittent bolus, propofol, sedation, TCI